2010
DOI: 10.1007/s11199-010-9833-z
|View full text |Cite
|
Sign up to set email alerts
|

College Men’s Third-Person Perceptions about Idealized Body Image and Consequent Behavior

Abstract: This study investigates college men's thirdperson perception in relation to body image factors using an experiment that involved a convenience sample of 148 male college students of Chinese descent in Singapore. The college men reported that the effects of media's idealized body images on female friends were greater than the effects on themselves. Their perception of media effects on the self was positively associated with their body dissatisfaction and intention to engage in body image behavior. Their percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 71 publications
(78 reference statements)
0
10
0
Order By: Relevance
“…Direct association between presumed influence and behavioral intentions, however, was either negative, opposing the hypothesis (when other women were considered), or nonsignificant (when other men were considered). In their study of male college students in Singapore, Chia and Wen (2010) found that perceived effects of media portrayals of ideal body images on male friends and female friends were unrelated to body dissatisfaction, intention of going on a diet or going to a gym regularly, but negatively related to intention of going through cosmetic surgery (for "male friends") and taking diet pills (for "female friends") respectively.…”
Section: Ideal Body Images On the Media And Body Dissatisfactionmentioning
confidence: 99%
“…Direct association between presumed influence and behavioral intentions, however, was either negative, opposing the hypothesis (when other women were considered), or nonsignificant (when other men were considered). In their study of male college students in Singapore, Chia and Wen (2010) found that perceived effects of media portrayals of ideal body images on male friends and female friends were unrelated to body dissatisfaction, intention of going on a diet or going to a gym regularly, but negatively related to intention of going through cosmetic surgery (for "male friends") and taking diet pills (for "female friends") respectively.…”
Section: Ideal Body Images On the Media And Body Dissatisfactionmentioning
confidence: 99%
“…Furthermore, our finding that preferences for muscularity were not influenced by the article has support in research that has shown that men's and women's drives for muscularity are not associated with their magazine reading habits (Cramblitt & Pritchard, 2013;Pritchard & Cramblitt, 2014). No priming of content affected people's judgments about their moderate fitness adherence or healthfulness, which we attribute to the measures themselves because they tapped moderation in fitness, and it is typically exposure to unrealistic ideal bodies that contributes to elevated body dissatisfaction (Bartlett et al, 2008;Chia & Wen, 2010;Richins, 1991).…”
Section: Discussionmentioning
confidence: 53%
“…Media sources convey to the public what the perfect man's and woman's body should look like. The Western idealized man's body is lean, large, and strong with a Vshape from broad shoulders (Burlew & Shurts, 2013;Chia & Wen, 2010), defined chest, arm, and abdominal muscles (Bartlett, Vowels, & Saucier, 2008), and a lean waist (Ryan & Morrison, 2009). For women, body ideals prescribe they be exceptionally thin (Grabe et al, 2008;Nemeroff, Stein, Diehl, & Smilack, 1994;Stice, Maxfield, & Wells, 2002) and toned (Nemeroff et al, 1994;Pritchard & Cramblitt, 2014).…”
Section: Does Fitness Priming Influence Self-and Other-judgments Of Pmentioning
confidence: 99%
“…In turn, people respond to the emphases the media place on body shape. For example, Chia and Wen (2010) showed that men who perused ads with idealized models had greater levels of body dissatisfaction and negative body image, and expressed more intention to diet, exercise routinely, and have cosmetic sur gery. Similar research results have been seen for women.…”
Section: Does Fitness Priming Influence Self-and Other-judgments Of Pmentioning
confidence: 99%